2021
DOI: 10.3390/brainsci11060806
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Direct Current Stimulation as a Treatment Tool for Mild Traumatic Brain Injury

Abstract: Mild traumatic brain injury (mTBI) has been defined as a transient (<24 h) condition of confusion and/or loss of consciousness for less than 30 min after brain injury and can result in short- and long-term motor and cognitive impairments. Recent studies have documented the therapeutic potential of non-invasive neuromodulation techniques for the enhancement of cognitive and motor function in mTBI. Alongside repetitive transcranial magnetic stimulation (rTMS), the main technique used for this purpose is trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 114 publications
0
2
0
1
Order By: Relevance
“…We are currently testing the next generation of allostatic neurotechnology which translates brain electrical activity to not only auditory tones, but also very low‐level electrical stimulation of the scalp. An elegant series of preclinical and clinical studies 53 , 54 , 55 , 56 , 57 , 58 , 59 suggest that highly localized electrical stimulation of the scalp, at levels so low that they are not consciously recognized, can have a significant impact on the brain. We will report these results for mTBI upon the completion of that study.…”
Section: Discussionmentioning
confidence: 99%
“…We are currently testing the next generation of allostatic neurotechnology which translates brain electrical activity to not only auditory tones, but also very low‐level electrical stimulation of the scalp. An elegant series of preclinical and clinical studies 53 , 54 , 55 , 56 , 57 , 58 , 59 suggest that highly localized electrical stimulation of the scalp, at levels so low that they are not consciously recognized, can have a significant impact on the brain. We will report these results for mTBI upon the completion of that study.…”
Section: Discussionmentioning
confidence: 99%
“…Electrical stimulation and assessment of the brain for the treatment of persistent concussion symptoms has long been considered for the treatment of TBI, and has emerged in recent years via several different modalities including transcranial direct current stimulation (tDCS), magnetoencephalography (MEG), and rTMS. Rudroff and Workman, 2021, conducted a comprehensive review of the effects of tDCS in mTBI [ 47 ]. The authors found just three studies that examined tDCS for mTBI, and concluded that there is high intersubject variability in outcomes and limited evidence that tDCS has a significant beneficial effect in mTBI.…”
Section: Discussionmentioning
confidence: 99%
“…Uma metanálise publicada em 2016 comparou estudos com ETCC e concluiu que a aplicação simultânea com TC gerou resultados melhores na memória operacional (HILL et al, 2016). Da mesma forma, Martin et al, (2014) BEGEMANN et al, 2020;DENDOCKER et al, 2016;HARA et al, 2021;RAZZA et al, 2021;RUDROFF et al, 2021).…”
Section: Discussionunclassified